Chemoenzymatic synthesis of hydroxytyrosol monoesters and their suppression effect on nitric oxide production stimulated by lipopolysaccharides. Issue 2 (1st February 2019) - Sakakura, Ayaka; Pauze, Martin; Namiki, Atsuhiro; Funakoshi-Tago, Megumi; Tamura, Hiroomi; Hanaya, Kengo; Higashibayashi, Shuhei; Sugai, Takeshi
ABSTRACT: Fatty acid monoesters of hydroxytyrosol [2-(3, 4-dihydroxyphenyl)ethanol] were synthesized in two steps from tyrosol (4-hydroxyphenylethanol) by successive Candida antarctica lipase B-catalyzed chemoselective acylation on the primary aliphatic hydroxy group over phenolic hydroxy group in tyrosol, and 2-iodoxybenzoic acid (IBX)-mediated hydroxylation adjacent to the remaining free phenolic hydroxy group. Examination of their suppression effects on nitric oxide production stimulated by lipopolysaccharides in RAW264.7 cells showed that hydroxytyrosol butyrate exhibited the highest inhibition (IC50 7.0 μM) among the tested compounds. Graphical abstract: : Hydroxytyrosol monoesters were site-selectively synthesized from tyrosol in two steps. Among them, butyrate showed strongest suppression effect on NO production stimulated by LPS.